Monitoring Guidelines for Home and Outpatient Parenteral Antibiotic Therapy - Alain Y Martel (Canadian Journal of Infectious Diseases)
When prescribing home intravenous antibiotic therapy (HIVAT), physicians must consider not only the factors normally considered in a hospital setting, but also the limitations and advantages of home therapy. Examples include dosage schedule, short and long term toxicity, stability of the antibiotics at room temperature after dilution, half-life of antibiotics, compatibility with other antibiotics or medications in the same bag and distribution methods from the supplier (pharmacy) to the patient. Consideration of these factors may direct antimicrobial choices, the mode of delivery and treatment schedule. Other prerequisites for antibiotic selection for home therapy include tolerability and low incidence of toxic reactions. Physicians and nurses must be aware of the adverse effects associated with prolonged outpatient intravenous antimicrobial therapy. Additional knowledge must include pharmacokinetics (absorption, distribution and elimination) and the pharmacodynamics (biochemical and physiological effects and mechanisms of action) of the commonly used antibiotics. One simple guideline is the less often a drug has to be administered, the more convenient the therapy will be for the patients, facilitating a higher rate of compliance. The less frequent administration schedules will also require less staff time for training and troubleshooting. Many antimicrobial agents can be given once daily and, therefore, readily meet this objective. Classes of antimicrobials that can be used once daily include aminoglycosides, ceftriaxone, vancomycin and the new quinolones. The development of antimicrobials that can be administered less often has been a major factor contributing to the growth of HIVAT. If an antibiotic has to be used more frequently than three times a day, the use of a computerized ambulatory infusion pump is helpful; however, pumps are expensive and not readily available. Other considerations for HIVAT include renal impairment, liver failure and hematological toxicities. These factors have led the author and colleagues to develop specific monitoring recommendations and techniques.